2021
DOI: 10.30574/wjarr.2021.9.1.0492
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity profile of uropathogenic Escherichia coli strains at the China-Guinea Friendship Hospital of Kipé in Conakry (Guinea)

Abstract: Introduction: Escherichia coli (E. coli) is one of the main bacterial species associated with urinary tract infections. Nowadays, this bacterium is becoming more and more resistant to antibiotics. Objective: The aim of this study was to determine the antibiotic sensitivity profiles of all strains of E. coli isolated from urine during the period from September 1st, 2018 to March 13th, 2019 at the Biomedical Laboratory of the China-Guinea Friendship Hospital of Kipé in Conakry. Materiel and Methods: Cultures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The cefoxitin resistance rate was 25.36%. A previous study in Guinea reported lower results [37]. Cefoxitin resistance in Escherichia coli strains was low in Niger compared to data from other countries.…”
Section: Discussionmentioning
confidence: 69%
“…The cefoxitin resistance rate was 25.36%. A previous study in Guinea reported lower results [37]. Cefoxitin resistance in Escherichia coli strains was low in Niger compared to data from other countries.…”
Section: Discussionmentioning
confidence: 69%
“…[13], showed that Carbapenems (Imipenem and Meropenem) represented the best option for the treatment of urinary tract infections caused by ESBL-producing strains [12,14]. However, Makanéra, et al [15] found that Cephalosporins, Penicillins and Monobactams should be used with β-lactamase inhibitors [15].…”
Section: Antibiotic Susceptibility Of Isolated Uropathogenic Germsmentioning
confidence: 99%
“…(16.2%) [5] . In Guinea, Makanera et al reported in their study published in 2021 a hign resistance of Escherichia coli to numerous antibiotics belonging to different families [12] . These authors reported before in 2020 the multi-resistance of Klebsiella pneumonia strains to antibiotics belonging to different families [13] .…”
Section: Introductionmentioning
confidence: 99%